Hypomethylation-induced regulatory programs in T cells unveiled by transcriptomic analyses - Lysandrou, Memnon; Stamou, Panagiota; Kefala, Dionysia; Pierides, Chryso; Kyriakou, Maria; Savvopoulos, Nikolaos; Christofi, Panayiota; Papadopoulou, Anastasia; Yannaki, Evangelia; Costeas, Paul; Spyridonidis, Alexandros (Frontiers in Immunology, 2023)
Regulatory T-cells (Tregs) are essential mediators of tolerance mitigating aberrant immune responses. While naturally occurring Treg (nTregs) development and function are directed by epigenetic events, induced Treg (iTregs) identity and mechanisms of action remain elusive. Mirroring the epigenetic circuits of nTregs, we and others have used hypomethylation agents (HA) to ex vivo convert T-cells into iTregs (HA-iTregs) and further showed that the suppressive properties of the HA-iTregs are predominantly confined in an emergent population which de novo expresses the immunomodulatory molecule HLA-G, consequently providing a surface marker for isolation of the suppressive HA-iTreg compartment (G + cells). We isolated the HA-induced G + cells and their G -counterparts and employed high-throughput RNA-sequencing (seq) analyses to uncover the G + -specific transcriptomic changes guiding T-cells towards a regulatory trajectory upon their exposure to HA. We found a distinct transcriptional upregulation of G + cells accompanied by enrichment of immune-response related pathways. Though single-cell RNA-seq profiling revealed regulatory G + cells to have molecular features akin to nTregs, when assessed in conjunction with the comparative transcriptomic analysis and profiling of secreted cytokines against the non-suppressive G -cells, FOXP3 and other T-helper signatures appear to play a minor role in their suppressive phenotype. We found an ectopic expression of IDO-1 and CCL17/22 in G + cells, denoting that in vitro exposure of T-cells to HA may well unlock myeloid suppressor genes. This report provides transcriptional data shaping the molecular identity of a highly purified and potent HA-iTreg population and hints towards ectopic myeloid-specific molecular mechanisms mediating HA-iTreg function.